Correction: Distinctive organized molecular assemble of MoS2, MOF and Co3O4, for efficient dye-sensitized photocatalytic H2 evolution. Issue 1 (29th November 2022) - Fan, Kai; Jin, Zhiliang; Wang, Guorong; Yang, Hao; Liu, Duanduan; Hu, Hongyan; Lu, Gongxuan; Bi, Yingpu
Abstract : Correction for 'Distinctive organized molecular assemble of MoS2, MOF and Co3 O4, for efficient dye-sensitized photocatalytic H2 evolution' by Kai Fan et al., Catal. Sci. Technol., 2018, 8, 2352–2363, ; https://doi.org/10.1039/C8CY00380G .